National-Cultural Specificity of the Realization of Moral Support in English Linguoculture: A Pragmatic and Linguocultural Perspective - Babayeva, Irada Sabirovna (The Lingua Spectrum, 2026)
Moral support constitutes one of the essential communicative mechanisms through which individuals maintain interpersonal relationships, regulate emotional well-being, and reinforce social solidarity. Although expressions of encouragement, sympathy, reassurance, and emotional assistance appear universal, their linguistic realization is strongly influenced by national culture, communicative traditions, and value systems. This study investigates the national-cultural specificity of moral support in English linguoculture from pragmatic and linguocultural perspectives. The research examines verbal strategies employed by native English speakers in situations involving emotional distress, failure, uncertainty, grief, and psychological pressure. Particular attention is devoted to politeness strategies, indirectness, emotional mitigation, empathy markers, supportive speech acts, and culturally conditioned communicative norms. The study integrates Speech Act Theory, Politeness Theory, Cultural Linguistics, and Intercultural Communication Theory to identify the linguistic and pragmatic mechanisms underlying moral support in English discourse. The findings demonstrate that English communicative culture emphasizes personal autonomy, emotional moderation, positive politeness, indirect encouragement, and face-saving strategies.